Identification and Analysis of Factors Improving Social Life in Urban Public Spaces with Focus on Enclosure and Sociability - Saeed Mohammadzade; Mohsen Ghasemi; Malihe Norozi; Mansor Nikpor (مسکن و محیط روستا)
The dominance of vehicles in the urban spaces of Iran has continuously decreased the human scale and degraded social values. Unfortunately, the issue of human-centered designs has been rejected in many cities of Iran. The central square of Bam city is one of these spaces. In this study, with regard to the importance of social life in public urban spaces as one of the main elements of the city and public sphere, the effective factors of improving social life in urban spaces are identified. The focus of this identification is on the element of enclosure and the role and significance of each factor in flourishing social activities. The nature of this study is descriptive-analytical, and it has a practical purpose. The study investigates the views of 83 participants in SPSS software with factor analysis and attractiveness measurement model. The results indicate that from a total of 35 identifiers extracted from the literature and the views of experts, 3 main factors (physical-spatial, activity-performance and preceptive-conceptual) are determined with 29 identifiers, which play a significant role in improving social life in urban spaces with focus on enclosure and sociability. Moreover, it was found out that the revitalization of these factors is important in improving social and optional activities without a ffecting compulsory activities. At the end, the results showed that enclosure is the fundamental principle of urban spaces and architectural design, and that the space is in fact begins with enclosures. The observance of the factors identified in this study may turn urban spaces to spaces that are sociable for people in connection with other principles of architectural design.